A THEORETICAL FRAMEWORK OF E-WALLET ADOPTION AMONG SMALL-SIZED MUSLIM MERCHANTS: AN APPLICATION AND EXTENSION OF TECHNOLOGY ACCEPTANCE MODEL - Nor Asiah Yaakub; Nathasa Mazna Ramli; Nurul Aini Muhamed; Sumaiyah Abd Aziz; Agoos Munalis Tahir (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The use of wallets is increasing rapidly, especially during the covid-19 pandemic due to movement control orders. E-wallets is a favourable choice of e-money transfer among younger and tech-savvy people and those who are at an advanced level in their lives influenced by the internet. Current research trends on e-wallet adoption emphasized on the customer side but dearth of academic work on merchant’s perspective. From literature, there is no thorough framework for e-wallet adoption. It is also worthy to highlight that the adoption rate amongst small merchants especially among Muslims is still low compared to numbers of established small business. The factors that influence the use of e-wallets among merchant users may differ from customer users due to the different purposes of using e-wallets. Furthermore, there is another religious factor, which is related to Islamic principles that are exclusively for Muslims where this might influence Muslim’s decision in adopting e-wallet. Thus, it is essential to address this issue since small-sized Muslim merchants representing the majority businesses in Malaysia. Their adoption of e-wallets will contribute to the world aim in achieving a cashless society. This study proposes a conceptual framework grounded from Technology Acceptance Model with extensions of other variables such as trust, technology efficacy, government support, and structural assurance as to explore the factors that influence merchants e-wallet adoption. This paper has made an initial effort to propose a comprehensive theoretical framework as a basis for a future research agenda. This also calls for empirical testing on the suggested variables in the context of small-sized Muslim merchants.